Nanodiagnosis and Nanotreatment of Cardiovascular Diseases: An Overview - Fakhara Sabir; Mahmood Barani; Mahwash Mukhtar; Abbas Rahdar; Magali Cucchiarini; Muhammad Nadeem Zafar; Tapan Behl; Simona Bungau (Chemosensors, 2021)
Cardiovascular diseases (CVDs) are the world’s leading cause of mortality and represent a large contributor to the costs of medical care. Although tremendous progress has been made for the diagnosis of CVDs, there is an important need for more effective early diagnosis and the design of novel diagnostic methods. The diagnosis of CVDs generally relies on signs and symptoms depending on molecular imaging (MI) or on CVD-associated biomarkers. For early-stage CVDs, however, the reliability, specificity, and accuracy of the analysis is still problematic. Because of their unique chemical and physical properties, nanomaterial systems have been recognized as potential candidates to enhance the functional use of diagnostic instruments. Nanomaterials such as gold nanoparticles, carbon nanotubes, quantum dots, lipids, and polymeric nanoparticles represent novel sources to target CVDs. The special properties of nanomaterials including surface energy and topographies actively enhance the cellular response within CVDs. The availability of newly advanced techniques in nanomaterial science opens new avenues for the targeting of CVDs. The successful application of nanomaterials for CVDs needs a detailed understanding of both the disease and targeting moieties.